A semi-analytical bearing model considering outer race flexibility for model based bearing load monitoring. (1st May 2018) - Kerst, Stijn; Shyrokau, Barys; Holweg, Edward
Highlights: Model based bearing load measurement has high potential for condition monitoring. A semi-analytical bearing model capturing raceway flexibility is proposed. Flexibility is captured by deformation shapes and a Fourier compliance approximation. Simulation results show an accurate representation of the element load distribution. An experimental study shows the potential of the model for bearing load monitoring. Abstract: This paper proposes a novel semi-analytical bearing model addressing flexibility of the bearing outer race structure. It furthermore presents the application of this model in a bearing load condition monitoring approach. The bearing model is developed as current computational low cost bearing models fail to provide an accurate description of the more and more common flexible size and weight optimized bearing designs due to their assumptions of rigidity. In the proposed bearing model raceway flexibility is described by the use of static deformation shapes. The excitation of the deformation shapes is calculated based on the modelled rolling element loads and a Fourier series based compliance approximation. The resulting model is computational low cost and provides an accurate description of the rolling element loads for flexible outer raceway structures. The latter is validated by a simulation-based comparison study with a well-established bearing simulation software tool. An experimental study finally shows the potential of the proposed model in a bearing load monitoring approach.